2021
DOI: 10.1002/pat.5492
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization ofchitosan‐gelatin/single‐walledcarbon nanotubes electrospun composite scaffolds for cartilage tissue engineering applications

Abstract: Cartilage is a connective tissue with a slow healing rate due to lack in blood circulation and slow metabolism. Designing tissue engineering scaffolds modified based on its specific features can assist its natural regeneration process. In this study, the chitosan-gelatin/single-walled carbon nanotubes functionalized by COOH (SWNTs-COOH) nanocomposite scaffolds were fabricated through electrospinning. The effect of each component and different duration of cross-linking were assessed in terms of morphology, poro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Electrospinning technique is considered a useful method for the fabrication of nanofiber materials. During the past decades, electrospinning was found to have numerous biomedical applications as tissue engineering, 28–30 sensing and drug delivery systems 6,30 as well as industrial applications such as in textile industries 31 …”
Section: Electrospinning Techniquementioning
confidence: 99%
“…Electrospinning technique is considered a useful method for the fabrication of nanofiber materials. During the past decades, electrospinning was found to have numerous biomedical applications as tissue engineering, 28–30 sensing and drug delivery systems 6,30 as well as industrial applications such as in textile industries 31 …”
Section: Electrospinning Techniquementioning
confidence: 99%
“…[14][15][16][17][18] Carbon nanotubes (CNTs) have emerged as a promising contender as scaffolds for the production of engineered cartilage. [19][20][21][22][23][24][25][26][27][28][29] This is largely due to their intrinsic ability to provide fibrous nanoscale topography resembling that of the ECM, 19,20,22 simulating the immediate environment that chondrocytes interact with in vivo. The addition of nanoscale topography has been shown to increase cell adhesion 19,24 and improve chondrocyte proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…23 King et al 22 demonstrated that woven textiles made from dry-spun multi-walled carbon nanotube (MWNT) yarns led to the production of key cartilaginous components, including collagen and aggrecan. Bahrami Miyanji et al 28 found that adding SWNTs to a chitosan-gelatin scaffold improved wettability, scaffold stability, and cell viability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, its properties lie between polymers and permanent implants, making it an ideal implant material. 9,[15][16][17] However, the major problem with using Magnesium as a material is its rapid corrosion rate when subjected to a chloride environment; hence, accelerated degradation is witnessed even before the completion of the healing process. [18][19][20][21] Although, various reinforcements have been brought into light for enhancing the properties of the Magnesium by providing it an adequate amount of strength and resistance to corrosion.…”
Section: Introductionmentioning
confidence: 99%